The role and importance good business negotiation skills for modern managers - Cvetković Filip; Kovačević S.Maja; Stanković Aleksandar; Andrejević Dejan; Filev Mihajlo (Ekonomija: teorija i praksa)
Negotiating represents a skill that is present in every aspect of life, whether it is everyday negotiations over simple matters, or business negotiations, which are the primary focus of this paper. Negotiation always occurs between two interested parties. This skill has existed as long as humankind, but it has never been as important as it is today. Trade gave rise to the phenomenon of negotiation, which, in ancient times, replaced violent seizure and theft. Today, business negotiation is a highly valued skill. Not every negotiator possesses a natural talent for negotiation, which is why many researchers have dedicated themselves to studying this skill, developing a wide range of theoretical frameworks to help people learn and refine their negotiation abilities. These foundational principles are the subject of this paper, along with the main elements of business negotiation, the characteristics of a successful negotiator, and numerous recommendations for honing business communication and negotiation skills. The aim of this research is to highlight the significance of the manager's role and to demonstrate that effective business negotiation requires knowledge, precision, and the ability to assess psychological factors.